The Right to Engage in Political Activity - Danielyan, Gevorg (Bulletin of Yerevan University C: Jurisprudence, 2022)
In this article the author examines the evolution of «political activity», adjacent terms of it (“politics”, “political resistance”, “political neutrality”, ect.), the content of their legal basis, which are causing widely disagreement nowadays, and a number of conclusions and recommendations were presented, which are aimed at the complex solution of the mentioned problems.The relevance of the topic is dictated as well regarded to some gaps about the above mentioned terms in international legal documents and experience. Particularly, a material of research were the following questions: What are the reasons for the provided restrictions? Why are they needed? While, there is not enough reference to the issues, what are the concrete components of such restrictions.In the framework of the scientific research it was, as possible, completely analyzed the legal basis of the terms, they were combined with the constitutional regulations and was discovered the legal content of each of them, the limits of the application, the features of the legal restrictions, due to the status of the subjects ect.The research is aimed to solve two problems: a) in case of obvious gaps in legislation regarded to above mentioned terms, to propose possibly acceptable solutions in practice b) to clearly outline the main directions of the domestic law, that are needed to be improved.
Keywords: politics; political activity; political resistance; political neutrality; depoliticization; party; judicial branch; President of the Republic